2015
DOI: 10.1152/ajplung.00208.2015
|View full text |Cite
|
Sign up to set email alerts
|

EET-dependent potentiation of pulmonary arterial pressure: sex-different regulation of soluble epoxide hydrolase

Abstract: We tested the hypothesis that suppression of epoxyeicosatrienoic acid (EET) metabolism via genetic knockout of the gene for soluble epoxide hydrolase (sEH-KO), or female-specific downregulation of sEH expression, plays a role in the potentiation of pulmonary hypertension. We used male (M) and female (F) wild-type (WT) and sEH-KO mice; the latter have high pulmonary EETs. Right ventricular systolic pressure (RVSP) and mean arterial blood pressure (MABP) in control and in response to in vivo administration of U4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 46 publications
7
24
0
Order By: Relevance
“…Consequentially, the suppression of Ephx2 mRNA is concomitantly associated with the same reduction in sEH protein levels ( Fig. 1 B and D), as we reported previously (9)(10)(11)(12)(13)20), demonstrating that regulation of sEH by estrogen is at the transcriptional level. We then indicated that DNA methylation is a crucial step in the estrogen/ER-governed regulatory process for Ephx2 expression.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consequentially, the suppression of Ephx2 mRNA is concomitantly associated with the same reduction in sEH protein levels ( Fig. 1 B and D), as we reported previously (9)(10)(11)(12)(13)20), demonstrating that regulation of sEH by estrogen is at the transcriptional level. We then indicated that DNA methylation is a crucial step in the estrogen/ER-governed regulatory process for Ephx2 expression.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, findings of estrogen-dependent suppression of sEH to increase tissue EETs in the cerebral circulation provide mechanistically based evidence for a female-favorable protection from cerebral ischemic damages (7,8). We have also provided evidence indicating that female-specific down-regulation of sEH protein expression in cardiac, pulmonary, and vascular tissues favors a greater contribution of EETs in females than males and initiates the same cardiovascular responses as those observed in male sEH-KO mice, or male mice treated with sEHIs (9)(10)(11)(12). Particularly in the microcirculation, a genetic deficiency in the Ephx2 gene or down-regulation of sEH expression elicits significantly enhanced flow/shear stress-induced vasodilation and attenuated pressure-induced vasoconstriction via an EET-dependent mechanism in the mesenteric, coronary, and skeletal muscle arterioles (9,11,13).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…During these processes, an EETdependent modulation of pressure-sensitive behavior was indicated for the first time that elucidates, at least in part, the mechanistic insights for EET-exerted cardioprotective properties in terms of an improvement in myocardial perfusion through a significant reduction in coronary resistance (26). Moreover, consistent with our previous findings showing a female-specific downregulation of sEH in arteries of skeletal muscle and mesentery (29), as well as in the pulmonary circulation (22) to potentiate the bioactivity of EETs, the present study indicates a female-favorable attenuation of myogenic constriction, as a function of suppression of sEH expression in the coronary circulation revealing, from a physiological point of view, the female-specific regulation that possesses universally based characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, E2 inhibits the expression/activity of soluble epoxide hydrolase (sEH), a key enzyme in EET metabolism [144]. Several studies linked low sEH activity to the pathophysiology of PAH: (1) E2-, genetic-, and pharmacologically-induced downregulation of sEH (and increased pulmonary EET) potentiates hypoxic pulmonary vasoconstriction [145][146][147]; (2) lungs from PH patients express no/little sEH; (3) hypoxia decreases the expression of sEH; and (4) when exposed to hypoxia, sEH KO mice exhibit exacerbated pulmonary vascular remodeling [147]. It seems that E2 plays a role in female-specific (physiological) downregulation of sEH, as suggested by the much higher sEH activity in male and OVX mice compared to intact female mice [148,149].…”
Section: Role Of Cyp1b1 and Estrogens In Arachidonic Acid Metabolismmentioning
confidence: 99%